TAMI-63. GLIOBLASTOMA ASSOCIATED MESENCHYMAL STEM LIKE CELLS (G-MSC) WHICH INFILTRATE TUMORS IN HUMAN AND MOUSE ARE STRONGLY ASSOCIATED WITH IMMUNOSUPPRESSION. (9th November 2020) - Dharma, Sanam; Figel, Sheila; Barone, Tara; Ciesielski, Michael; Fenstermaker, Robert
Abstract: Glioblastoma (GBM) is the most aggressive form of brain cancer with an overall survival (OS) less than 16 months. Glioblastoma associated mesenchymal stem like cells (G-MSC) were identified in human patient samples, and higher presence of these cells in patient samples co-relates with lower overall survival. Our lab and others have also identified these cells in orthotopic GL261 glioblastoma murine models. We hypothesize that infiltration of G-MSC plays a key role in creating the highly immunosuppressive environment seen in GBMs. In order to investigate this, we utilized data from the TCGA database to stratify patients into two groups, showing higher or lower expression of the G-MSC markers (CD73, CD90, CD105). Patients expressing higher levels of G-MSC markers showed higher expression of CD4+ cells, as compared to patients with lower G-MSC marker expression. Further, patients with higher G-MSC markers showed high levels of PTGS2, the gene encoding cyclooxygenase 2 (COX2), a known tumor growth promoting and immunosuppressive molecule. We further investigated CD4+ T cell infiltration using GL261 orthotopic implants and observed that CD4+ T cells positively corelated with levels of G-MSC in these tumors. Our studies indicate that levels of G-MSC co-relate with immune cell infiltration and the expression of immunosuppressive factors such as COX2, underlining the importance of these cells in immunosuppression-driven resistance to therapy. These studies will be later utilized to develop rationale combination therapies to improve the overall survival in GBM.